Approach to the Assessment and Management of Pediatric Patients With Atopic Dermatitis: A Consensus Document. Section IV: Consensus Statements on the Assessment and Management of Pediatric Atopic Dermatitis. Issue 5 (November 2019) - Lansang, Perla; Lara-Corrales, Irene; Bergman, James N.; Hong, Chih-ho; Joseph, Marissa; Kim, Vy H.D.; Lam, Joseph M.; Landells, Ian; Marcoux, Danielle; Prajapati, Vimal H.; Ramien, Michele L.; Spring, Shanna
This document is intended to provide practical guidance to physicians treating pediatric atopic dermatitis (AD), especially dermatologists, pediatricians, allergists, and other health-care professionals. The recommendations contained here were formalized based on a consensus of 12 Canadian pediatric dermatologists, dermatologists, pediatricians, and pediatric allergists with extensive experience managing AD in the pediatric population. A modified Delphi process was adopted with iterative voting on a 5-point Likert scale, with a prespecified agreement cutoff of 75%. Topic areas addressed in the 17 consensus statements reflect areas of practical management, including counselling, assessment, comorbidity management, and therapy.